Functional Integration of Sport Sciences Graduates into Primary Care for Non-Communicable Disease Prevention: A Cross-National Ecological Evaluation of 34 Countries - Hosam Zidan; Nasser Abouzeid; Anwar Al-Nuaim; Mohamed A. Hassan (International Journal of Environmental Research and Public Health, 2026)
Globally, physical activity is increasingly acknowledged as an effective strategy for combating non-communicable diseases (NCDs). However, there is a significant global disparity in the integration of sport sciences graduates (SSGs) into national health systems. This study assessed the professional roles of SSGs within healthcare systems and their association with NCD mortality across (n = 34) countries that met the selection criteria, using a cross-national, ecological, and cross-sectional design. Principal component analysis was conducted to reduce the dimensions of the correlated structural indicators. A pre-specified generalized linear model (Gamma family, log link) with HC3 robust standard errors estimated the association between SSG integration and age-standardized NCD mortality, alongside a descriptive analysis of public funding (national or subnational) for SSG services. The findings indicate that integrating SSGs into primary care was associated with approximately 23% lower age-standardized NCD mortality (rate ratio 0.77, 95% CI 0.63–0.94, p = 0.011; approximately 16% to 23% across model specifications) after adjusting for demographic and economic factors, with near-universal public funding (100% of integrated versus 24% of other countries; Fisher’s exact p < 0.001). To our knowledge, this is the first cross-national analysis to link the functional integration of SSGs into primary care with population NCD mortality, and this relationship remained consistent across multiple robustness checks. The implications suggest that functional integration and its public funding may represent promising policy approaches for strengthening preventive health services. Given the ecological, cross-sectional design, longitudinal studies are warranted to establish causality.